BUILDING RESILIENCE OF UKRAINIAN UNIVERSITIES IN THE FACE OF MILITARY INTERVENTION: EXPLORING FORMS AND IMPLICATION (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
This article explores the concept of organizational resilience in higher education institutions, which can enable them to deal with unexpected events, recover from crises, and contribute to future success. Despite the growing academic interest in resilience, there is a lack of consensus on its definition and how it works, highlighting the need for additional knowledge on the capabilities and conditions that make up sustainability. The authors contribute to this field by conceptualizing resilience as a meta capacity and breaking it down into three stages:  adaptation, transformation, and anticipation. They also identify core capabilities, including strategic vision, operational flexibility, and a supportive culture, that form organizational resilience. Drawing on process research, the authors provide an overview of the relationship and interaction between the different stages of resilience, as well as the main prerequisites and driving forces. They also propose four tools based on an analysis of European normative-legal acts that can restore stability in crisis situations. This study advances understanding of the complex and built-in construct of organizational resilience and offers insights that can inform future empirical work in this area. The article underscores the significance of cultivating resilience capabilities in higher education institutions, particularly during times of turbulence and ambiguity, to guarantee their enduring.